Porous fiber materials can alleviate the risk of farmland drought and flooding disasters and prompt crop growth - Qin, Tianling; Liu, Shanshan; Li, Wei; Xu, Shu; Lu, Jie; Lv, Zhenyu; Abebe, Sintayehu A. (Frontiers in Plant Science, 2023)
Floods and droughts on farmland seriously damage agricultural production. Porous fiber materials (PFM) made from mineral rocks have high porosity, permeability, and water retention and are utilized widely in green roofs and agricultural production. Therefore, studying the impact of PFM on the improvement of farmland is of great importance for soil and water conservation. We set 64 extreme rainfall to analyze the impact of PFM on soil water content (SWC), runoff, nutrient loss, microorganism, and plant growth. Our study emphasizes that the effectiveness of PFM for soil improvement is mainly reflected in three aspects: First, PFM with high porosity can increase soil water holding capacity and timely replenish the water lost from the surrounding soil. Second, PFM with high permeability can increase infiltration during rainfall and decrease runoff and nutrient loss, reducing the risk of farmland flooding and pollution. Finally, PFM consists of gold ions and alkali metal oxides, which can stabilize agglomerates and improve soil enzyme activity, organic matter, and others. Improving the soil environment can increase the relative abundance of some microbial strains, promoting soil nitrogen fixation, cellulose degradation, and phosphate dissolution. Finally, when PFM was buried in the soil, the SWC and nutrients improved wheat yield by -6.7% to 20.4%. However, due to the structural characteristics of PFM, when the rainfall amount was low or the PFM volume was large, PFM couldn't store water sufficiently during rainfall, which seriously reduced the maximum saturated moisture content and water absorption performance. Meanwhile, the PFM could not release water in time and replenish the soil water deficit, which increased drought risk and reduced microbial biodiversity. Eventually, the maize filling process was hampered, and the yield decreased by 5.1% to 42.5%. In conclusion, the appropriate volume of PFM and irrigation system may enhance soil water storage capacity, minimize agricultural pollution, and promote crop production, which helps alleviate farmland drought and floods and promote crop growth.